Priorities for Intervention to Restore Ancient Cities after Disasters ((Case Study Old Aleppo)) (Damascus University Journal for engineering sciences, 2025)
People seek to return to their normal lives after disasters as soon as possible, but it takes time to assess the situation, agree on common goals, and see rebuilding. Disaster and destruction are only one part of the picture, while the rest depend on the agencies' ways of responding to disasters. And the effects of that response on the development of the affected countries, as it constitutes a second disaster and a source of great concern in the event that the priorities for intervention to restore the urban heritage are not appropriate, so it is necessary to adopt methods and priorities for recovery that are not harmful in the long run.            The current situation generally refers to the challenge of restoring destroyed heritage in the historic city centers of the Middle East, especially in Old Haab after more than ten years of war, and given that there is almost no practical experience in restoring urban heritage after conflict, it is important to define a special approach. For such important recovery sites and intervention priorities.            Hence the importance of defining sectoral priorities based on the intersection of intervention priorities with historical, functional and architectural divisions. Priority setting aims to address the problems of limited resources in their various forms, from the lack of time required for implementation and the lack of funding sources. It works to unify and direct resources to achieve the greatest productivity at the lowest possible cost.
Keywords: Priorities for intervention; Disaster Management; - Old Aleppo; - Cities at Risk; restoration of the urban fabric